Social Ethics In The Perspective Of Hadith Regarding Honoring Capital - Erima Sari Siregar; Azhar Nasution; Siti Kholidah Marbun (Al-Mu'tabar, 2026)
This study examines the concept of honoring guests in the perspective of hadith through a structured literature review of scientific works published between 2016 and 2025. Employing a qualitative descriptive design, this research identifies, classifies, and analyzes twenty scholarly articles sourced from Google Scholar using the keyword “memuliakan tamu.” The findings show that the theme appears across multiple fields, including Islamic studies, education, social sciences, and cultural studies, with publication trends rising significantly during 2022–2024. Institutional distribution reveals that most studies originate from academic institutions in Java, followed by Sumatra, Sulawesi, and Kalimantan, indicating broad scholarly engagement across Indonesia. Thematically, the literature emphasizes that honoring guests is deeply connected to ethical, moral, and spiritual values rooted in hadith and Qur’anic teachings. Although numerous studies have been conducted, a research gap remains, as previous works often address only specific aspects without providing an integrated synthesis. Therefore, this study contributes a comprehensive understanding of the principles and significance of guest hospitality in Islam and highlights its role as a social ethic that promotes harmony, compassion, and communal solidarity.